Developing system on urban health using crowdsourcing method: A case study of dengue outbreak - Mokraoui, Lyes; Mohd. Noor, Norzailawati (Asian Association on Remote Sensing, 2016)
The alarming increase in number of dengue fever (DF) cases in the world and particularly in Malaysia has made the disease one of the top priorities for its government. Over the years Malaysia has been collecting statistics about the disease and the vector itself. This study aims in collecting historical dengue occurrences and looking at the favorable conditions in which the mosquito thrives. The research aims at breaking the life cycle of the vector and the disease gradually by developing a system that would collect and process crowd sourced data and other factors i.e weather and moon phase to generate a dengue index.Moon phases, weather conditions, landuse type and data from crowedsourcingare the study factors of this research. A collection of dengue cases numbers from the ministry's of health in Malaysia (MOH) has been compiled and correlated with some of these factors. Preliminary results have shown that dengue cases correlate with the moon phases,drought and raining seasons. This confirms that in Malaysia there is a relationship between the moon cycles and the mosquito’s night activity; this can be used as a short cycle factor alongside the raining-draught long cycles.We have further developed a method to monitor and break the life cycle of the vector of the dengue outbreaks in Malaysiathrough civic engagement followed by civic awareness by knowing high activity period the biting habit of the mosquito and by calculating the spatial correlation of non-temporal factors, intensive measures can be taken by the relevant authorities to forewarn the citizens. We believe that this system can be implemented in the immediate in the region saving lives and resources.